2021
DOI: 10.1016/j.ajem.2021.01.072
|View full text |Cite
|
Sign up to set email alerts
|

The ongoing impact of COVID-19 on asthma and pediatric emergency health-seeking behavior in the Bronx, an epicenter

Abstract: Background: The Bronx has the highest prevalence of asthma in the United States (US), and was also an early COVID-19 epicenter, making it a unique study location. Worldwide reports describe significant declines in pediatric emergency department (PED) visits during COVID-19. The ongoing impact of COVID-19 on all PED presentations, including asthma, at an early epicenter has not been studied beyond the pandemic peak and into the early phases of state re-opening. Objectives: To compare PED health-seeking behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…Similar results were also reported from Taiwan 28 and Slovenia 29 . Others also suggested a significant decrease in asthma‐related paediatric emergency visits 25,26 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were also reported from Taiwan 28 and Slovenia 29 . Others also suggested a significant decrease in asthma‐related paediatric emergency visits 25,26 …”
Section: Discussionsupporting
confidence: 77%
“…Reports from western countries suggested that COVID‐19‐related lockdowns significantly decreased asthma‐related attendance to primary care, and hospital admission, with no corresponding increase in asthma deaths 23‐26 . However, there is a lack of data about the impact of NPI measures on paediatric asthma exacerbation admissions in developing countries where resources are limited and health service utilisations are believed to have been negatively impacted by COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is consistent with prior literature reporting a decrease in healthcare utilization during the pandemic, particularly hospitalizations and emergency department visits. [ 8 , 9 , 10 , 11 ]. However, our study adds to the sparse literature, by evaluating 79 clinics across four large, academic institutions in the Southeastern US, indicating decreased utilization of pediatric primary care [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has resulted in a significant decrease in pediatric emergency department visits and hospitalizations. [ 8 , 9 , 10 , 11 ]. There has also been a decrease in pediatric primary care visits due to concerns about children becoming infected with SARS-CoV-2, or in order to comply with stay-at-home orders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation